Adherence to the Mediterranean diet and risk of gestational diabetes: a prospective cohort study - Fatemeh Mohtashaminia; Fatemeh Hosseini; Ahmad Jayedi; Majid Mirmohammadkhani; Alireza Emadi; Leila Takfallah; Sakineh Shab-Bidar (BMC, 2023)
Abstract Background Limited data is available on the association between adherence to the Mediterranean diet during early pregnancy and risk of gestational diabetes (GDM) in countries located in the Middle East, one of the regions with the highest prevalence of GDM. Methods A total of 647 pregnant mothers were included in the present prospective birth cohort study in Iran. Dietary intake was assessed by a 90-item food frequency questionnaire during the first trimester of pregnancy. Cases of GDM were ascertained by a two-step approach with a 50-g screen followed by a 100-g oral glucose tolerance for those who tested positive. Cox proportional hazard model was used to calculate the hazard ratio and 95%CI of GDM across tertiles of the Mediterranean diet score, while controlling for a wide range of potential confounders. Results A total of 647 pregnant mothers were included, of whom 77 mothers were diagnosed with GDM during their pregnancy. The average age of the mothers was 28.8 ± 5.1 years. In the multivariable analysis, being in the third tertile of the score of adherence to the Mediterranean diet was associated with a 41% lower risk of developing GDM as compared to those in the first tertile (adjusted hazard ratio: 0.59, 95%CI: 0.35, 0.99). Conclusions Based on our findings, greater adherence to the Mediterranean diet during early pregnancy may be associated with a lower risk of developing GDM in Iranian women. Larger cohort studies are needed to confirm the findings.